(untitled) (Transport systems and technologies, 2018)
This paper represents the search for methodological foundations of the isothermal rolling stock certification, namely insulated covered carriages. There were analyzed the existent requirements to the technical passports and their informational content. There were offered several ways of improving the standard technical documentation, and the main directions of scientific researches designed to improve the efficiency of use of isothermal carriages. The results showed that the introduction of thermal characteristics to this specific carriage passport will allow to objectively evaluating their possibility to transport perishable goods during the entire life cycle.